Match characteristics of women`s and men`s singles and doubles events in elite badminton - Hoffmann, D.; Brinkschulte, M.; Vogt, T. (International Journal of Performance Analysis in Sport, 2026)
Currently, a comprehensive match data collection for badminton does not yet exist. Competition analyses in badminton commonly focus on the singles events, while there is a lack of knowledge of the event characteristics of men`s and women`s doubles as well as mixed doubles. To date, no study has investigated all five events at the highest international tournament level. However, knowledge of the time structure in a given discipline is essential for elite badminton coaches to set specific training drills. Therefore, we analysed the time structure of matches played across all events at the 2018 Badminton World Federation Championships. Our results showed that game duration was longer in women`s doubles than in mixed doubles. Women`s doubles consisted of the longest rally times and highest percentage of real-time played. The rest time, rest time between games and total points played did not differ between the disciplines. Men`s doubles and mixed doubles were characterised by the shortest rally times and highest shot frequencies. Our findings confirmed the assumed differences in the time structures between these five events. Coaches should apply a differentiated approach to training elite badminton players and implement specific training drills, such as "multi-shuttle drills" with event-specific frequencies.